A Novel Lipid Biomarker Panel for the Detection of Heart Failure with Reduced Ejection Fraction. (6th January 2020) - Mueller-Hennessen, Matthias; Düngen, Hans-Dirk; Lutz, Matthias; Trippel, Tobias Daniel; Kreuter, Michael; Sigl, Johanna; Müller, Oliver J; Tahirovic, Elvis; Witt, Henning; Ternes, Philipp; Carvalho, Susan; Peter, Erik; et al.
Abstract: OBJECTIVES: In this study we aimed to identify novel metabolomic biomarkers suitable for improved diagnosis of heart failure with reduced ejection fraction (HFrEF). METHODS: We prospectively recruited 887 individuals consisting of HFrEF patients with either ischemic (ICMP, n = 257) or nonischemic cardiomyopathy (NICMP, n = 269), healthy controls (n = 327), and patients with pulmonary diseases (n = 34). A single-center identification (n = 238) was followed by a multicenter confirmation study (n = 649). Plasma samples from the single-center study were subjected to metabolite profiling analysis to identify metabolomic features with potential as HFrEF biomarkers. A dedicated analytical protocol was developed for the routine analysis of selected metabolic features in the multicenter cohort. RESULTS: In the single-center study, 92 of 181 metabolomic features with known chemical identity (51%) were significantly changed in HFrEF patients compared to healthy controls ( P <0.05). Three specific metabolomic features belonging to the lipid classes of sphingomyelins, triglycerides, and phosphatidylcholines were selected as the cardiac lipid panel (CLP) and analyzed in the multicenter study using the dedicated analytical protocol. The combination of the CLP with N-terminal pro–B-type natriuretic peptide (NT-proBNP) distinguished HFrEF patients from healthy controls with an area under the curve (AUC) of 0.97 (sensitivity 80.2%, specificity 97.6%) and was significantly superior compared to NT-proBNP alone (AUC = 0.93, sensitivity 81.7%, specificity 88.1%, P <0.001), even in the subgroups with mildly reduced left ventricular EF (0.94 vs 0.87; P <0.001) and asymptomatic patients (0.95 vs 0.91; P <0.05). CONCLUSIONS: The new metabolomic biomarker panel has the potential to improve HFrEF detection, even in mild and asymptomatic stages. The observed changes further indicate lipid alterations in the setting of HFrEF.